Dronedarone: current evidence for its safety and efficacy in the management of atrial fibrillation - Schweizer, Patrick Alexander; Becker, Rüdiger; Katus, Hugo; Thomas, Dierk (Drug design, development and therapy, 2011)
Dronedarone: current evidence for its safety and efficacy in the management of atrial fibrillation Patrick A Schweizer, Rüdiger Becker, Hugo A Katus, Dierk ThomasDepartment of Cardiology, Medical University Hospital, Heidelberg, GermanyAbstract: Atrial fibrillation (AF) is the most common sustained arrhythmia. Management of AF includes rate control, rhythm control if necessary, prevention of thromboembolic events, and treatment of the underlying disease. Rate control is usually achieved by pharmacological suppression of calcium currents or by applying β-blockers or digitalis compounds. In contrast, the number of compounds available for rhythm control is still limited. Class Ic agents increase mortality in patients with structural heart disease, and amiodarone harbors an extensive side effect profile despite its efficacy in maintaining sinus rhythm. Furthermore, rhythm control by these compounds has not been shown to reduce patient mortality. Dronedarone is a new antiarrhythmic drug that has been developed to provide rhythm and rate control in AF patients with fewer side effects compared with amiodarone. This review primarily focuses on clinical trials evaluating efficacy and safety of the novel drug. Conclusions from these studies are critically reviewed, and recommendations for clinical practice are discussed. Dronedarone significantly reduced the incidence of hospitalization due to cardiovascular events or death in high-risk patients with atrial fibrillation (ATHENA trial). However, dronedarone was less efficient than amiodarone in maintaining normal sinus rhythm (DIONYSOS trial) and is contraindicated in severe or deteriorating heart failure (ANDROMEDA trial). In summary, dronedarone represents a valuable addition to the limited spectrum of antiarrhythmic drugs and is currently recommended in patients with paroxysmal and persistent AF to achieve rate and rhythm control, excluding cases of severe or unstable congestive heart failure.Keywords: dronedarone, atrial fibrillation, antiarrhythmic therapy